Kaum Muhajirin Dan Anshor Sebagai Teladan Generasi Milenial (Analisis Tafsir al-Misbah) - Tri Lestari Masruchin; Ahmad Isnaeni; Bukhori Abdul Shomad; Masruchin Masruchin (Journal Khafi : Journal Of Islamic Studies, 2024)
Abstract / Abstrak The story of the Muhajirin and the Ansar imparts values of noble character in human life. Their struggle in assisting the Prophet Muhammad (peace be upon him) in spreading the religion, upholding the truth, and building a civil society was filled with tears and blood. Through a literature review analyzing the verses about the Muhajirin and Ansar, it can be concluded that their resilient attitude, willingness to leave behind wealth, family, and power for the sake of Islam, mutual assistance, love for their brothers, courageous spirit, loyalty to their leaders, and fostering Islamic brotherhood are commendable traits. This can provide contributions and motivation for contemporary Muslims, especially the millennial generation, to become a better, more moral, and character-driven generation. Kisah kaum Muhajirin dan kaum Anshor memberikan nilai-nilai kehidupan manusia yang akhlakul karimah. Perjuangannya dalam membantu Nabi Muhammad Saw menyiarkan agama, menegakan kebenaran dan membangun negara yang madani, dipenuhi dengan air mata dan darah. Melalui kajian kepustakaan dengan menganalisa ayat-ayat kisah Muhajirin dan Nashor memberikan kesimpulan bahwa sikap mereka yang tangguh, rela meninggalkan harta, keluarga dan tahta demi Islam, saling tolong menolong, mencintai saudaranya, memiliki jiwa pemberani, sikap loyalitas terhadap pemimpin dan menjalin ukhuwah Islamiyah. Mampu memberikan kontribusi dan motivasi bagi umat Islam masa kini hususnya generasi milenial agar menjadi generasi yang lebih baik, bermoral dan berkarakter.